2004
DOI: 10.1007/s00277-004-0987-z
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoeosinophilia associated with malaria infection determined in the Sysmex XE-2100 hematology analyzer

Abstract: Hemozoin is known to be an end product of hemoglobin digestion by the malaria parasite. Hemozoin is a birefringent crystal, and thus hemozoin-containing white blood cells (WBCs) may show the atypical light scattering pattern. The purpose of this study was to investigate pseudoeosinophilia associated with malaria infection using a Sysmex XE-2100 hematology analyzer (Sysmex Corporation, Kobe, Japan). The study group included 16 patients with malaria infection. Of these, 38% showed erroneously high eosinophil cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 13 publications
2
28
2
1
Order By: Relevance
“…4,21 More recently, using the XE-2100 analyzer, two case series in South Korea, one with 16 and one with 3 P. vivax -infected patients, described pseudoeosinophilia and abnormal granulocyte-coded events in the DIFF scatterplot in approximately 38% of samples. 9,10 In 2008, Huh and others 5 in South Korea compared these two findings against thick-film malaria diagnosis in 144 samples of P. vivax -infected patients and in 319 samples from febrile patients, reporting a sensitivity of 69.4% and a specificity of 100%. 5 Other small case series have described similar findings 6,24 in P. vivax infected samples, and a case describing an elevated reticulocyte/IRF ratio and an increase in highly fluorescent lymphocyte-coded events in the DIFF scatterplot [DIFF(II) area] in a P. falciparum -infected patient 25 has been published by the Sysmex Corporation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,21 More recently, using the XE-2100 analyzer, two case series in South Korea, one with 16 and one with 3 P. vivax -infected patients, described pseudoeosinophilia and abnormal granulocyte-coded events in the DIFF scatterplot in approximately 38% of samples. 9,10 In 2008, Huh and others 5 in South Korea compared these two findings against thick-film malaria diagnosis in 144 samples of P. vivax -infected patients and in 319 samples from febrile patients, reporting a sensitivity of 69.4% and a specificity of 100%. 5 Other small case series have described similar findings 6,24 in P. vivax infected samples, and a case describing an elevated reticulocyte/IRF ratio and an increase in highly fluorescent lymphocyte-coded events in the DIFF scatterplot [DIFF(II) area] in a P. falciparum -infected patient 25 has been published by the Sysmex Corporation.…”
Section: Discussionmentioning
confidence: 99%
“…5,9 Huh and others 5 found that ≥ 5% pseudoeosinophilia in P. vivax -infected samples had a sensitivity of 38.9% and a specificity of 100%. We found that the optimal P. vivax -diagnostic pseudoeosinophilia was 20.9% and had an accuracy of 60.5% (95% CI = 51.1-69.9%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Recent studies from South Korea investigated pseudoeosinophilia and abnormal white blood cell (WBC) scattergrams of vivax malaria-infected patients on a Sysmex XE-2100 hematology analyzer (Sysmex Corporation, Kobe, Japan). 7,8 Because the sensitivity and specificity of these methods were apparently high, its application to early detection can lead to a significant reduction in patients' morbidity and mortality. 2,8 Previous studies had limitations of a rather small patient number and their inaccurate evaluation of parasitemia.…”
mentioning
confidence: 99%
“…2,11 Several authors have described pseudoeosinophilia or abnormal WBC scattergrams as a result of hemozoin-containing neutrophils using the Sysmex XE-2100 analyzer. 7,8,12 The Sysmex XE-2100 analyzer differentiates eosinophils from neutrophils based on side light-scattering differences. The neutrophils may show considerable side light scattering because of the birefringent character of hemozoin, and therefore, hemozoin-containing neutrophils may be incorrectly classified as eosinophils or two atypical eosinophil populations and two neutrophil populations.…”
mentioning
confidence: 99%